Pemberian Kombinasi Pupuk AB Mix dan Pupuk Organik Cair Limbah Rumah Tangga pada Tanaman Tomat (Lycopersicum esculentum Mill.) Secara Hidroponik - Yulinda Ari Indah Karunia; Fetmi Silvina; Murniati Murniati Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of application AB mix and liquid organic fertilizer from household waste and to get the best combination in supporting tomato growth and yield. The study conducted in the greenhouse of the Faculty of Agriculture, University of Riau, from January to April 2018. The research was an experiment consisting of five treatments arranged in a completely randomized design (CRD) and four replications. Combined AB mix with household waste POC consisting of T1: 1⁄4 AB Mix + 3⁄4 POC household waste, T2: 1⁄2 AB Mix + 1⁄2 POC household waste, T3: 3⁄4 AB Mix + 1⁄4 POC household waste, T4: AB Mix and T5: POC household waste. The results showed that the AB mix and combined with household waste POCs can accelerate flowering and increase the number of flowers, number of fruits per plant and total weight of fruit per plant. The application of fertilizer AB mix combined with household waste POC for best growth and yield of tomato plants, namely ¼ AB mix + ¾ POC household waste.Keywords: Tomato, AB mix, liquid organic fertilizer from household waste